Effect of piston clearance on the lubrication performance in axial piston pump. Issue 1 (29th August 2019) - Lee, Bora; Yu, Yonghun; Cho, Yong-Joo
Abstract : Purpose: This paper aims to provide a reliable and efficient numerical piston–cylinder design method and assess the effect of clearance on the piston-cylinder lubrication. Design/methodology/approach: Numerical analyses of lubrication characteristics were performed for the piston–cylinder interface. The axial piston was numerically modeled, and the film pressure was calculated using the unsteady two-dimensional Reynolds equation. The behavior of the piston was analyzed by calculating the eccentricity satisfying the force and moment balance. Findings: The secondary motion of the piston included numerically simulated several cycles until the piston behavior converged, and contact with the inner wall of the cylinder and friction region was estimated. Results showed that the piston–cylinder clearance affected the contact force, length of the contact region and leakage flow rate. Originality/value: This result improves the understanding of the piston–cylinder lubrication and suggests considerations in terms of lubrication in clearance design.